The Barometer of Agency: Reconceptualising the 'Guided Reading' Teaching Approach - Maria Nicholas (MDPI AG, 2022)
The guided reading teaching approach is a commonly utilised practice that teachers have employed for over 20 years, both in Australia and abroad. What the approach entails, however, can be open to interpretation-an outcome that highlights the challenge of describing and conceptualising the approach in clear and unambiguous terms. This study addressed this issue of ambiguity by exploring whether guided reading, rather than being a singular teaching strategy in-and-of-itself, can more accurately be reconceptualised as comprising a range of teaching strategies that educators move between from lesson beginning to lesson's end. Following thematic analysis of the six most commonly prescribed texts used in Australian Initial Teacher Education literacy units, a new model was devised as presented in this paper; a model that teachers and researchers in Australia and abroad can draw upon to better understand, apply and/or evaluate their own and other's use of the guided reading teaching approach in everyday practice.